Two new taxa of Bursera (Burseraceae) of Baja California Sur, Mexico - León de la Luz, José Luis; Pérez-Navarro, José Juan (Instituto de Ecología, A.C., 2010)
We describe and illustrate two new taxa of Bursera from the Cape Region in the southern sector of the Baja California Peninsula, Mexico. One is named B. littoralis and the other B. rupicola. The former is morphologically related to B. filicifolia and B. laxiflora of the southern peninsula and still with B. ribana of western Mexico, but differs in its smaller leaves and leaflets, the shrubby habit with dense and intricate branching, and in its habitat on the coastal dunes. The second taxon is related to B. epinnata of the southern peninsula, differing from it in its almost always unifoliolate, shiny, and membranaceous leaves with scattered simple and glandular trichomes, short inflorescences with few flowers and particularly in its shrubby growth habit with pendent branches. Both species belong to the Bullockia section, having a bilocular ovary, bivalvate fruit, well developed cataphylls, 4(5)-merous flowers, and non-exfoliating bark.